2000
DOI: 10.3904/kjim.2000.15.3.236
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Biatrial Myxoma in a Young Female Patient : Case Report

Abstract: We report a case of multicentric, biatrial cardiac myxoma in a 29-year-old female who complained of exertional dyspnea, abdominal distension and peripheral edema. Any other associated skin lesions, breast mass or endocrine disorder presenting complex form were not seen on her. Also, there was no contributory medical history, hypertension and diabetes mellitus. By using transthoracic echocardiography, we identified a biatrial myxoma attached to the interatrial septum. During surgical excision, we found a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…This differs from the case we describe above, where one sizable mass grew from one atrium via an ASD into the opposite side of the heart. 4 , 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from the case we describe above, where one sizable mass grew from one atrium via an ASD into the opposite side of the heart. 4 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and surgical excision are essential in order to prevent embolization and sudden death. 2 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…An LA mass after excision of LA myxoma has been described due to residual 2 or additional masses, such as biatrial, 3 as well as multicentric 4 myxomas or a thrombus. Another common mimic is an inverted LA appendage, which usually everts and disappears with cardiac filling.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, the location of the myxoma was in the left atrium in 17 patients (81%) and right atrium in 4 patients (19%) with no reported ventricular or multicentric myxoma. In the literature, few cases of multicentric non-familial bi-atrial myxoma were reported [11][12][13][14]. Additionally, ventricular locations of the myxoma were reported rarely in other case series.…”
Section: Discussionmentioning
confidence: 99%